1981
DOI: 10.1042/bj2000457
|View full text |Cite
|
Sign up to set email alerts
|

Labelling of membrane glycoproteins on rat spermatozoa collected from different regions of the epididymis

Abstract: The major glycoprotein on the plasma membrane of testicular spermatozoa labelled with the galactose oxidase/NaB3H4 technique has mol.wt. 110 000. As spermatozoa pass through the epididymis, labelling of this glycoprotein disappears and is replaced by labelling of a 32 000-mol.wt. protein. The latter protein is a major component of epididymal secretions. The evidence suggests that it is inserted into or absorbed on to the plasma membrane, and since its appearance on spermatozoa correlates with the acquisition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

1983
1983
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(26 citation statements)
references
References 14 publications
0
26
0
Order By: Relevance
“…A llOK component is the major surface glycoprotein of rat testicular spermatozoa labeled with the glucose oxidase-tritium borohydride technique, but it is not labeled on cauda epididymal spermatozoa by this procedure (Jones et al, 1981a;Brown et al, 1983). Also, lactoperoxidase-catalyzed iodination studies indicated that rat caput epididymidal sperm have surface components of 94K, 72K, and 59K, which are not iodinated on cauda sperm (Olson and Danzo, 1981).…”
Section: Sperm Surface Components Are Altered During Epididymal Maturmentioning
confidence: 99%
“…A llOK component is the major surface glycoprotein of rat testicular spermatozoa labeled with the glucose oxidase-tritium borohydride technique, but it is not labeled on cauda epididymal spermatozoa by this procedure (Jones et al, 1981a;Brown et al, 1983). Also, lactoperoxidase-catalyzed iodination studies indicated that rat caput epididymidal sperm have surface components of 94K, 72K, and 59K, which are not iodinated on cauda sperm (Olson and Danzo, 1981).…”
Section: Sperm Surface Components Are Altered During Epididymal Maturmentioning
confidence: 99%
“…Radiolabeled MT used in this study has the native conformation conserved as much as possible and reacts with the MT antibody which recognizes the N112-terminal . During the maturation of spermatozoa in the epididymis, it is well known that many proteins are adsorbed to the cell membrane (Faye et al 1980;Jones et al 1981). The binding site of MT is of course not known, but this result suggested that MT binding to the spermatozoa is mainly a nonspecific form and partly a specific form.…”
Section: Discussionmentioning
confidence: 99%
“…Rat CD52, previously named the 'major maturation-associated sperm membrane antigen' (Zeheb and Orr, 1984;Moore et al, 1989), an approximately 26 kDa protein (Myles, 1993), and sperm membrane glycoprotein (SmemG) (Eccleston et al, 1994) may be an example of such a glycoprotein. Rat CD52 was originally identified as the principal molecule labelled by surface carbohydrate-labelling experiments using intact mature spermatozoa from the cauda epididymidis (Olson and Hamilton, 1978;Jones et al, 1981;Brown et al, 1983;Zeheb and Orr, 1984;Hamilton et al, 1986;Olson et al, 1987;Moore et al, 1989;Eccleston et al, 1994). Furthermore, carbohydrate labelling of rat sperm glycoproteins on western blots in vitro (Pera et al, 1997) showed an unexpectedly high selectivity: the only molecule accessible to the periodate oxidation reaction was the counterpart of CD52.…”
Section: Introductionmentioning
confidence: 99%